2011
DOI: 10.1002/hep.24178
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for distinct pathways of hepcidin regulation by acute and chronic iron loading in mice

Abstract: In response to iron loading, hepcidin synthesis is homeostatically increased to limit further absorption of dietary iron and its release from stores. Mutations in HFE, transferrin receptor 2 (Tfr2), hemojuvelin (HJV), or bone morphogenetic protein 6 (BMP6) prevent appropriate hepcidin response to iron, allowing increased absorption of dietary iron, and eventually iron overload. To understand the role each of these proteins plays in hepcidin regulation by iron, we analyzed hepcidin messenger RNA (mRNA) responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
233
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(257 citation statements)
references
References 27 publications
18
233
2
4
Order By: Relevance
“…Considering iron metabolism upon certain chronic physiological alternation, the end-point of iron-related studies are normally set over 1 month after ovariectomy when using ovariectomized models (Ikeda et al, 2012;Liu et al, 2006;Mattace Raso et al, 2009). Moreover, a previous study by Ramos et al has demonstrated that hepcidin expression were distinct in response to long-term (3 weeks) or acute (1 day) iron loading (Ramos et al, 2011). To this end, we decided to address a long-time effect of chronic estrogen deficiency on systemic iron homeostasis.…”
Section: Elevated Hepcidin Expression In Liver Devoid Of Endogenous Ementioning
confidence: 99%
“…Considering iron metabolism upon certain chronic physiological alternation, the end-point of iron-related studies are normally set over 1 month after ovariectomy when using ovariectomized models (Ikeda et al, 2012;Liu et al, 2006;Mattace Raso et al, 2009). Moreover, a previous study by Ramos et al has demonstrated that hepcidin expression were distinct in response to long-term (3 weeks) or acute (1 day) iron loading (Ramos et al, 2011). To this end, we decided to address a long-time effect of chronic estrogen deficiency on systemic iron homeostasis.…”
Section: Elevated Hepcidin Expression In Liver Devoid Of Endogenous Ementioning
confidence: 99%
“…On the other hand, most high fat diet models induce metabolic changes but not fibrosis [66,67] . Furthermore, introduction of iron in the diet can create secondary effects by up-regulating liver hepcidin synthesis and thereby inhibiting the expression of iron exporter, ferroportin [68][69][70] . This will then lead to sequestration of iron in Kupffer cells and trigger inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we show that TGF-␤1 mRNA levels are increased in mouse models of iron overload and that TGF-␤1 contributes to hepatocyte hepcidin activation via an ALK5 and Smad1/5-dependent signaling pathway. We speculate that TGF-␤1 may contribute to the iron-mediated hepcidin response and may be the factor that mediates increased hepcidin levels in iron-loaded BMP6 KO mice (4).…”
Section: Tgf-␤1 Stimulated Smad1/5/8 Phosphorylation and Hepcidin Indmentioning
confidence: 93%
“…Hepcidin expression is regulated by several signals, including plasma iron levels, hepatic iron stores, inflammation, erythropoietic activity, and hypoxia (2). Plasma iron levels and hepatic iron stores activate BMP6-ALK2/3-Smad1/5/8 signaling through a yet poorly defined mechanism to transcriptionally modulate hepcidin synthesis (3)(4)(5). Notably, hepcidin can be mildly increased upon chronic iron loading of BMP6 knock-out mice, suggesting that the BMP6 pathway does not completely account for the iron response of hepcidin (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation